2020
DOI: 10.1186/s12955-020-01623-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived changes of specific attitudes, perceptions and behaviors during the Corona pandemic and their relation to wellbeing

Abstract: Background During the COVID-19 pandemic, most people had to cope with the restrictions of the lockdown, leaving them to their fears, insecurity and isolation. On the other hand, due to the unexpected ‘extra time’ there was room for new experiences and for personal reflections on what is essential in life, to perceive nature and relations more consciously etc. We, therefore, intended to analyze perceived changes of attitudes and behaviors during the time of lockdown, and whether these perceptions would contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 66 publications
(113 citation statements)
references
References 32 publications
1
101
0
3
Order By: Relevance
“…In fact, the second lockdown followed in December 2020. However, also (non-tumor) persons recruited in June 2020 were “irritated by statements about danger and course of the infection in public media”, but to a lower extend (44%) (Büssing et al 2020b ). In contrast, Musche et al ( 2020 ) reported that tumor patients had no higher distress scores or anxiety compared to healthy persons, while tumor patients had more adherence safety behavior (indicating that they are more aware of their risks) and more dysfunctional safety behaviors (indicating that they nevertheless are afraid of the unpredictable pandemic outcomes).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the second lockdown followed in December 2020. However, also (non-tumor) persons recruited in June 2020 were “irritated by statements about danger and course of the infection in public media”, but to a lower extend (44%) (Büssing et al 2020b ). In contrast, Musche et al ( 2020 ) reported that tumor patients had no higher distress scores or anxiety compared to healthy persons, while tumor patients had more adherence safety behavior (indicating that they are more aware of their risks) and more dysfunctional safety behaviors (indicating that they nevertheless are afraid of the unpredictable pandemic outcomes).…”
Section: Discussionmentioning
confidence: 99%
“…For that purpose, training to mindful awareness might be helpful to facilitate wondering awe and subsequent feelings of gratefulness—despite the restrictions. As discussed, awe/gratitude are among the best predictors of perceived changes due to the pandemic and contribute to a person’s wellbeing (Büssing et al 2020b ). Others reported that such feelings of awe are related to a sense of connection and belonging (Prade and Saroglou 2016 ), which can be seen as a stabilizing resource, too.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor patients, for example, perceived nature and silence and also their relationships more intensely, some had a stronger interest in spiritual issues, while others perceived loneliness and ruminated worrying reflections (2). In a survey among a more general population from Germany, these perceived changes were operationalized and measured in terms of (1) Nature/Silence/Contemplation, (2) Spirituality, (3) Relationships, (4) Reflection on life, and (5) Digital media use (8). Strongest changes were observed for Relationships and Nature/Silence/Contemplation.…”
Section: Introductionmentioning
confidence: 99%